FIFA World CupTM 2010 in South Africa - Andrews, Katrin (Diplomica Verlag, 2011)
HauptbeschreibungAfter the era of apartheid, festivals, conferences and events such as the hosting of the FIFA World Cup 2010TM provide exciting opportunities to market South Africa as preferred tourist destination. The exposure to international media and their audiences will have significant impact on the country's tourism industry and will generate benefits for the local economy. These benefits include an increase in economic growth and job creation, social and infrastructural transformation as well as the alleviation of poverty. In order to induce sustainable contributions to the country's.